2022
DOI: 10.1007/s10578-022-01324-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Parenting and Child Behaviour Problems and the Moderating Effect of Child Callous Unemotional Traits in Foster and Biological Families

Abstract: The goals of the current study were to examine (i) differences in parenting between foster and biological parents, (ii) the longitudinal associations with children’s internalising and externalising problems and iii) the potential moderation of these by children’s callous-unemotional traits (CU traits). Data from 86 foster children (M = 4.44 years, male = 48%) and 148 biological children (M = 3.69 years, male = 49%) with their families were analysed in a longitudinal study with three measurement times. Parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Furthermore, in a sample of adolescents living in either foster or birth families, Joseph et al ( 2014 ) reported an association between foster care group and higher APSD-CU scores, while controlling for age, sex, IQ, maternal education, and single-parent household status. Schutte et al ( 2022 ) also found that young children in foster care had higher ICU scores than their peers in birth families. Navarro-Soria et al ( 2020 ) found a similar pattern of results across different analyses, showing higher CU traits (measured by the CABI-LPE) in children in foster care compared to non-foster/comparison children (controlling for sex and age), though children who had longer stays in foster care did not significantly differ in CU traits compared to comparison children when father reports were included for the latter group.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, in a sample of adolescents living in either foster or birth families, Joseph et al ( 2014 ) reported an association between foster care group and higher APSD-CU scores, while controlling for age, sex, IQ, maternal education, and single-parent household status. Schutte et al ( 2022 ) also found that young children in foster care had higher ICU scores than their peers in birth families. Navarro-Soria et al ( 2020 ) found a similar pattern of results across different analyses, showing higher CU traits (measured by the CABI-LPE) in children in foster care compared to non-foster/comparison children (controlling for sex and age), though children who had longer stays in foster care did not significantly differ in CU traits compared to comparison children when father reports were included for the latter group.…”
Section: Resultsmentioning
confidence: 95%
“…Eight records were included, with samples from Romania ( k = 2), Germany ( k = 2), Finland ( k = 1), U.K. ( k = 1), Spain ( k = 1), and Canada ( k = 1). Six of the eight relevant studies (Campbell et al, 2004 ; Humphreys et al, 2015 ; Joseph et al, 2014 ; Lindberg et al, 2009 ; Navarro-Soria et al, 2020 ; Schutte et al, 2022 ) examined the association between past or current experiences of AC (coded categorically) and CU/psychopathic traits. Meanwhile, three studies (Krischer & Sevicke, 2008 ; Kumsta et al, 2012 ; Navarro-Soria et al, 2020 ) provided data concerning associations between amount of time or number of placements in AC and levels of CU/psychopathic traits.…”
Section: Resultsmentioning
confidence: 99%